2007
DOI: 10.1074/jbc.m701332200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Specific Proteolytic Processing of Bone Sialoprotein and Bone Acidic Glycoprotein-75 with Mineralization within Biomineralization Foci

Abstract: Mineral crystal nucleation in UMR 106-01 osteoblastic cultures occurs within 15-25-m extracellular vesicle-containing biomineralization foci (BMF) structures. We show here that BAG-75 and BSP, biomarkers for these foci, are specifically enriched in laser capture microscope-isolated mineralized BMF as compared with the total cell layer. Unexpectedly, fragments of each protein (45-50 kDa in apparent size) were also enriched within captured BMF. When a series of inhibitors against different protease classes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 53 publications
3
63
0
Order By: Relevance
“…The primary biological function of IBSP is unclear, although it has been reported to be involved in the initiation of matrix mineralization through the nucleation of hydroxyapatite crystals [40,41]. Furthermore, it has been proposed that IBSP is required to undergo fragmentation, possibly through the actions of serine proteases, in order to allow for efficient matrix mineralization [15,42,43]. In this report, we were able to demonstrate colocalization of HTRA1 and IBSP in osteo-induced mASC spheroid cultures, thus confirming the potential for endogenous HTRA1 to interact with IBSP under osteogenic culture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary biological function of IBSP is unclear, although it has been reported to be involved in the initiation of matrix mineralization through the nucleation of hydroxyapatite crystals [40,41]. Furthermore, it has been proposed that IBSP is required to undergo fragmentation, possibly through the actions of serine proteases, in order to allow for efficient matrix mineralization [15,42,43]. In this report, we were able to demonstrate colocalization of HTRA1 and IBSP in osteo-induced mASC spheroid cultures, thus confirming the potential for endogenous HTRA1 to interact with IBSP under osteogenic culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the osteogenic genes that were regulated by HTRA1, IBSP held particular relevance to this study due to the fact that its ability to regulate mineral deposition has previously been reported to be dependent on the actions of serine proteases [15]. Attention was therefore focused on IBSP and its potential involvement in mediating the effects of HTRA1 on both osteogenesis of MSCs and mineralization of differentiating bone-forming cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix vesicles have long been contested as sites of nucleation in bone and recent data suggested that the vesicles are present in bone but that they vary in size and the composition (Gorski, 2011). Vesicles have also been shown to be present within biomineralization foci (Huffman et al, 2007). Biomineralization foci (10-25 micron diameter) are the result of ECM-mediated nucleation.…”
Section: Mineral Composition and Mechanisms Of Biomineralizationmentioning
confidence: 99%
“…In terms of protein, osteocyte-enriched control bone extracts contained an 18-kDa MBTPS1 fragment band also enriched in laser microscope-dissected biomineralization foci (Fig. 1a), sites of initial deposition of hydroxyapatite in osteoblastic cultures (29).…”
Section: Mbtps1 Mrna and Protein Are Deleted In Osteocyte-enriched Bomentioning
confidence: 99%